Anuran diversity and community structure in Lesti upriver across buffer zone habitat in Bromo Tengger Semeru National Park - Fathoni, Muhammad; Hakim, Luchman; Kurniawan, Nia (Universitas Brawijaya, 2022)
In Bromo Tengger Semeru National Park (BTSNP), buffer zone areas, one of which is the Lesti upstream rivers, play a critical role in sustaining biodiversity and community life. Frogs serve as a bioindicator of environmental change, particularly in the upstream rivers of the Lesti. The present study examines the diversity and community structure of Anura in the upstream rivers of Lesti, which are included in the BTSNP buffer zones. Throughout the surveys, up to 14 anuran species were encountered in four sites adjacent to the BTSNP border and crossed by the Lesti rivers. This study suggests that buffer zones may support herpetofaunal diversity by allowing humans to interact with them and sustainably utilize the resources in the areas. Urban development and conservation in these areas must be kept current in order to minimize environmental disruption caused by humans.